Bionomics Of Aedes Aegypti And Aedes Albopictus In Relation To Dengue Incidence On Penang Island And The Application Of Sequential Sampling In The Control Of Dengue Vectors - Phon, Chooi Khim (2007)
Satu kajian telah dijalankan untuk menentukan taburan dua jenis vektor denggi, Aedes aegypti dan Aedes albopictus di Kampung Paya Teluk Kumbar